2000
DOI: 10.1038/labinvest.3780117
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine Growth Regulation of CD30 Ligand in CD30-Expressing Reed-Sternberg Cells: Distinction Between Hodgkin's Disease and Anaplastic Large Cell Lymphoma

Abstract: SUMMARY:Persistent expression of high levels of CD30 in Hodgkin's Reed-Sternberg (H-RS) cells and anaplastic large-cell lymphoma (ALCL) cells, but not in most T-or B-cell lymphomas, suggests the presence of an underlying mechanism leading to the abnormality and possible involvement of CD30 in the growth and survival of these two unique types of tumors. In this study, we examined the effect of CD30 ligand (CD30L) on CD30-positive H-RS and ALCL cells in long-term cultures or in primary cultures. CD30L induced va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 45 publications
0
35
0
Order By: Relevance
“…CD30, as other members of the TNFR family, is able to promote cell survival as well as cell death (Duckett and Thompson, 1997;Amakawa et al, 1996). Previous studies have shown that activation of the CD30 receptor results in activation and enhanced proliferation of Hodgkin's lymphoma cells by activation of NF-kB (Lee et al, 1996(Lee et al, , 1997, but to induce an antiproliferative eect in anaplastic large cell lymphoma (ALCL) (HuÈ binger et al, 1999;Hsu and Hsu, 2000) and other CD30-positive cell lines, which has been described as induction of cell . Western blotting analysis was performed using whole cell lysate and anti-p53 or anti-actin antibody (b) Genomic DNA was extracted from JB6 and Karpas 299 cells and used for PCR ampli®cation of four genomic regions of p53 (exon 5, exon 6, exon 7, exon 8/9).…”
Section: Discussionmentioning
confidence: 99%
“…CD30, as other members of the TNFR family, is able to promote cell survival as well as cell death (Duckett and Thompson, 1997;Amakawa et al, 1996). Previous studies have shown that activation of the CD30 receptor results in activation and enhanced proliferation of Hodgkin's lymphoma cells by activation of NF-kB (Lee et al, 1996(Lee et al, , 1997, but to induce an antiproliferative eect in anaplastic large cell lymphoma (ALCL) (HuÈ binger et al, 1999;Hsu and Hsu, 2000) and other CD30-positive cell lines, which has been described as induction of cell . Western blotting analysis was performed using whole cell lysate and anti-p53 or anti-actin antibody (b) Genomic DNA was extracted from JB6 and Karpas 299 cells and used for PCR ampli®cation of four genomic regions of p53 (exon 5, exon 6, exon 7, exon 8/9).…”
Section: Discussionmentioning
confidence: 99%
“…Such autocrine interactions via CD30 and its ligand have also been described in Hodgkin lymphoma. 45,46 Whether CD30 signaling in neoplastic mast cells, like in anaplastic large cell lymphoma cells, triggers NF-kB-mediated increased survival needs to be addressed in further functional studies. 47 The immunohistochemical and molecular demonstration of expression of CD30 by mast cells predominantly in the aggressive variants of mastocytosis may have important consequences for patients with this disease in several respects.…”
Section: Cd30 In Advanced Mastocytosismentioning
confidence: 99%
“…23,24 CD30L has diverse biologic activity in different CD30ϩ cancers, ranging from enhancement of survival to no induction of apoptosis and cell cycle arrest. 14,[25][26][27][28][29] These paradoxical effects are caused by a differential effect on NF-B activation.…”
Section: Cd30 Receptor and Cd30l (Cd153)mentioning
confidence: 99%